2020
DOI: 10.31349/revmexfis.66.388
|View full text |Cite
|
Sign up to set email alerts
|

Experimental setup for the production of ultracold strongly correlated fermionic superfluids of 6Li

Abstract: We present our experimental setup to produce ultracold strongly correlated fermionic superfluids made of a two-component spin-mixture of 6Li atoms. Employing standard cooling techniques, we achieve quantum degeneracy in a single-beam optical dipole trap. Our setup is capable of generating spin-balanced samples at temperatures as low as T/TF = 0.1 containing up to 5 × 10^4 atomic pairs. We can access different superfluid regimes by tuning the interparticle interactions close to a broad magnetic Feshbach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The setup and methods employed to produce ultracold samples are described in detail in reference [21]. We are able to produce ultracold Fermi superfluids formed by a two-component spin mixture of 6 Li atoms in the two lowest hyperfine states |F = 1/2, m F = ±1/2 .…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 1 more Smart Citation

Faraday Waves in strongly interacting superfluids

Hernández-Rajkov,
Padilla-Castillo,
del Río-Lima
et al. 2021
Preprint
Self Cite
“…The setup and methods employed to produce ultracold samples are described in detail in reference [21]. We are able to produce ultracold Fermi superfluids formed by a two-component spin mixture of 6 Li atoms in the two lowest hyperfine states |F = 1/2, m F = ±1/2 .…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…In this way, we can manipulate ω r independently of ω z by varying the ODT power. To excite the superfluid, we modulate the ODT intensity by means of an acousto-optic modulator (AOM) [21], this allows us to control the radial frequency profile over time. All excitations studied in this paper are generated by periodically modulating the power of the ODT beam in the form…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%

Faraday Waves in strongly interacting superfluids

Hernández-Rajkov,
Padilla-Castillo,
del Río-Lima
et al. 2021
Preprint
Self Cite
“…Analyzing finite range interactions is of relevance since, while indeed, the BEC-BCS crossover has been identified in several systems, mostly in ultracold atomic clouds [23,24,[57][58][59][60], in some others the effective interaction is fixed and the crossover is tuned by means of the density [23,24,28,38,61] and, while the strength of the interaction is still characterized by the s-wave scattering length, it has been observed that next leading-order contributions, such as the effective range, are important for the density-induced BEC-BCS crossover, even at the mean-field level [28,38,62]. At any rate, the main requirement is the use of a finite-range interaction, a feature of the present study, and which has been known to pose a very difficult problem for solving the gap equation [62].…”
Section: Final Remarksmentioning
confidence: 99%
“…Now, if the atoms are fermions, for instance, i = 1 in 6 Li, or bosons i = 3/2 in 7 Li, we then face a formidable problem of a large number of coupled spin states or channels for two atoms. Fortunately, experimentalists are capable of preparing precise mixtures of hyperfine states in free or largely separated states [47]. Technically, this means that in the scattering channels at infinity one knows that the state is |f 1 , m 1 ; f 2 , m 2 〉 ± where f l , m l are the hyperfine quantum numbers of f = s + i and the suffix ± indicates symmetric (bosons) or antisymmetric (fermions) linear combinations.…”
Section: Scattering Of Two Atoms Involving Two Internal Channelsmentioning
confidence: 99%